AN OVERVIEW ON PLANTS WITH ANTI-INFLAMMATORY POTENTIAL - Pushpa, Karale; Mahesh, Karale (International Journal of Current Pharmaceutical Research, 2017)
Inflammation is a protective mechanism of the body which involves vascular tissues, plasma proteins or cells and chemical mediators for the removal of hazardous stimuli like pathogens, allergens, irritants or cell damage and initiates the healing process. Anti-inflammatory drugs like steroidal and non-steroidal anti-inflammatory drugs are used to treat inflammation. Recently, the synthetic drugs shows a number of side effects such as kidney failure, ulceration and bleeding, liver damage etc. Therefore a search for the other substitute with no or less side effects is necessary. Plants are used from ancient times to treat various serious disorders. Plant constitutes a large number of chemicals which are responsible for the treatment of disease in an archaistic manner. The present review was pile up various plants with anti-inflammatory potential.